PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI BERBASIS APLIKASI BENIME - Faishol, Riza; Sukardi, Sukardi (INCARE, International Journal of Educational Resources, 2023)
This research is based on the need for learning media that can attract the interest of grade XI MA Al-Fatah students in learning. The research uses research and development (r&d) using the borg and gall development model, which has ten steps, but researchers took only seven steps: 1) potential problems, 2) demand analysis, 3) product design, 4) design validation, 5) design revision, 6) product trials, 7) product revision. Research data is obtained from interviews, observations, teacher ratings, and students, validation tests by media and materials experts and documentaries of photos. The results of this study show that learning video products are valid and suitable for use in class XI MA which refers to the results of the media feasibility test from material experts of 74.2%, and the results of the feasibility test from media experts of 94.6%. The student response to the media got a percentage of 90%. Meanwhile, the results of the assessment by teachers on the media got a percentage of 92%. Based on the results of the feasibility test by experts and the responses of students and teachers, this learning video is suitable for use in the learning process. So it can be interpreted that using benime animation-based learning video products can increase students' enthusiasm for learning in class XI MA moral creed material.